The Impact Of Psychoeducation On Self-Efficacy And Motivation To Comprehend Treatment In Breast Cancer Patients (Ca Mammae) - Wahana, Hijratun; Yunita, Yunita; Tajaruddin, Muhammad; Negara, Candra Kusuma (Sean Institute, 2024)
Introduction: Breast cancer is not just a medical issue but also a psychological one. Individuals with cancer are susceptible to many psychological problems, including anxiety, sadness, stress, fear, and other related difficulties. Psychoeducation is a kind of psychological treatment that involves providing education to breast cancer patients to address their psychological concerns. Method: This study employs a quasi-experimental research methodology. The research focused on breast cancer patients. The study sample consisted of 50 respondents selected using the purposive sampling approach. The variable not influenced by this study is psychoeducation, whereas its dependent variables are self-efficacy and motivation. The data were gathered using General Self-Efficacy questionnaires, Intrinsic Motivation Inventory, and observation sheets. Statistical tests, namely the Paired T-Test and Independent Result: The study findings indicate significant improvements in self-efficacy (p = 0.000) and motivation (p = 0.000). Conclusion: This study demonstrates that psychoeducation has an impact on the self-confidence and drive to undertake treatment in breast cancer patients. Psychoeducation provides cancer-related knowledge on breast cancer and offers strategies to manage stress effectively. This may enhance self-efficacy and motivation among breast cancer patients undergoing treatment.